Enhancement of dielectric properties of PMMA:TIO₂ nanocomposite for organic field effect transistors / Lyly Nyl Ismail - Ismail, Lyly Nyl (Institute of Graduate Studies, UiTM, 2015)
In this thesis, a composite between poly (methyl methacrylate) (PMMA) with titanium dioxide (TiO₂) films were synthesized, fabricated and characterized using sol-gel spin coating technique. The dielectric, electrical and physical properties of PMMA:TiO₂ nanocomposite films was were investigated, to be used as the dielectric layer in the metal-insulator-semiconductor (MIS) device and organic field effect transistors (OFET) application. The goal of this study is to enhance the dielectric properties of PMMA with the influence of TiO₂nanopowder (high-k) material in the PMMA. Another goal is to overcome the leakage current (tunnelling current) and high operating voltage in MIS and OFET devices. PMMA:TiO₂ nanocomposite dielectric films deposition parameters were optimized resulting in good dielectric, electrical and physical properties. Results from the parameter optimization showed that the dielectric properties of PMMA:TiO2 nanocomposite film, which is focusing on the real permittivity, ε’, imaginary permittivity, ε’’ and capacitance were improved. The real permittivity, ε’ of PMMA:TiO2 nanocomposite film was 12 and 10 measured at 1 kHz and 1MHz, respectively…